2011
DOI: 10.1007/s00423-011-0883-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of abdominal shape index of patients on laparoscopy-assisted distal gastrectomy for early gastric cancer

Abstract: Accumulation of fat did not affect short-term surgical outcomes except for the duration of surgery and intraoperative blood loss in male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 29 publications
3
41
2
Order By: Relevance
“…Overall operative time was included in the majority of studies and was the only reported outcome that was associated with obesity in a majority of publications (Table ) . Among the 70 studies that included operative time as an outcome metric, 42 (60%) reported that obesity was associated with a longer operative time …”
Section: Resultsmentioning
confidence: 99%
“…Overall operative time was included in the majority of studies and was the only reported outcome that was associated with obesity in a majority of publications (Table ) . Among the 70 studies that included operative time as an outcome metric, 42 (60%) reported that obesity was associated with a longer operative time …”
Section: Resultsmentioning
confidence: 99%
“…Details of the LG procedures performed at WMUH have been previously described [4, 15]. The basic extent of lymph node dissection in the present series is D1+ or D2 [14].…”
Section: Methodsmentioning
confidence: 99%
“…LG has several benefits for GC patients, such as reduced pain, early recovery of intestinal function, and shorter hospital stay [24]. LG still has several drawbacks, however, including the limited range of movement, amplification of hand tremors, and inconvenient surgical positioning.…”
Section: Introductionmentioning
confidence: 99%
“…8,15,16 We performed laparoscopy-assisted distal gastrectomy (LADG) when the lesion was located in the antrum or the body of the stomach and laparoscopy-assisted total gastrectomy (LATG) when the lesion was located in the cardia. D1 + lymph node (LADG: No.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…[5][6][7] In contrast, laparoscopy-assisted gastrectomy (LAG) represents a less invasive surgical technique in terms of reduced postoperative morbidity, rapid return of the gastrointestinal function, a shortened hospital stay after surgery, reduced adhesions, and superior cosmetic results. 8 Several RCTs have already proven its feasibility based on surgical outcomes. 9,10 Therefore, in case of synchronous GC and CRC, performing simultaneous laparoscopic resection may be feasible.…”
mentioning
confidence: 99%